Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Ukuran Dewan Komisaris Terhadap Islamic Social Reporting Dan Reaksi Pasar Di Jakarta Islamic Index Tahun 2014-2017 - Anggi Pratiwi Sitorus (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2019)
This study discusses about There are many factors that influence the disclosure of Islamic Social Reporting. among them are Company Size, Board of Commissioners Size, Company Age, Profitability, Leverage, Company Profile and Management Ownership, and focused on Company Size Influence, Profitability and Board of Commissioners' Size on Islamic Social Reporting and its impact on Market Reaction. became the dominant factor of its direct influence on the Islamic Social Reporting (ISR), and the direct influence of market reaction and direct influence through the reaction of Islamic Social Reporting to Companies Registered in the Jakarta Islamic Index (JII) in 2014-2017. To answer this problem, Path analysis techniques are used. In answering this problem by providing a descriptive description with a quantitative approach.From the analysis of the results of data processing. The research produces answers to the above problems. The size of the company does not affect it directly to the response but influences it not directly through the Market Reaction. Thus the size of entrepreneurs is not separated from Islamic Social Reporting (ISR) and other variable variants, national karma together - the same as the significance of Market Reactions. The size of the Board of Commissioners influences directly on the Market Reaction that does not affect if it is through Islamic Social Reporting (ISR), with meaning the Size of Board of Commissioners also not through Islamic Social Reporting (ISR). There is no correlation between the size of the company, the profitability, the size of the board of commissioners and Islamic Social Reporting, there is no correlation between the size of the company, the profitability, and the size of the board of directors of Islamic Social Reporting and the market reaction.